PENGARUH QUICK RATIO, DEBT TO EQUITY RATIO, TOTAL ASSETS TURNOVER, RETURN ON ASSETS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SUB-SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2020 - Rakhmi Amaroh; Benny Osta Nababan; Muhlis Muhlis; Randi Deswardi (Economicus : Jurnal Ekonomi dan Manajemen, 2022)
The manufacturing industry continues to experience increasingly fierce competition so that many companies want good performance and experience profit growth every year. This study aims to determine the effect of the Quick Ratio, Debt to Equity Ratio, Total Assets Turnover, and Return on Assets to Profit Growth either partially or simultaneously. The method used is a quantitative method with the type of causality associative research. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange and the sample used in this study is food and beverage sub-sector manufacturing companies for the 2015-2020 period. The results of this study indicate that partially the Quick Ratio and Total Assets Turnover have a negative but significant effect on Profit Growth, the Debt to Equity Ratio has a negative but not significant effect on Profit Growth, and the Return on Assets has a positive and significant effect on Profit Growth. Simultaneously, it shows that all independent variables have an effect on Profit Growth.